2005
DOI: 10.1256/qj.05.88
|View full text |Cite
|
Sign up to set email alerts
|

JRA‐25: Japanese 25‐year re‐analysis project—progress and status

Abstract: SUMMARYThe progress and status of a new atmospheric re-analysis, JRA-25 the Japanese 25-year Re-analysis which covers the 26 years from 1979 to 2004, are introduced. Observational data include some newly produced for JRA-25 and advantages and drawbacks of performance are briefly described. JRA-25 has many advantages such as its handling of precipitation amounts, tropical cyclone analysis, and the extent of low-level cloud along western continents that are among the best compared to other re-analyses. The snow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 7 publications
0
76
0
1
Order By: Relevance
“…Onogi et al (2005Onogi et al ( , 2007 provide details. Briefly, while JRA-25 draws from the same basic satellite and conventional data streams as NCEP and ERA-40, the system assimilates satellite radiances rather than retrieved profiles, an approach which avoids trends and variability due to changes introduced in satellite data processing over the years.…”
Section: The Ncep/ncar and Jra-25 Reanalysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Onogi et al (2005Onogi et al ( , 2007 provide details. Briefly, while JRA-25 draws from the same basic satellite and conventional data streams as NCEP and ERA-40, the system assimilates satellite radiances rather than retrieved profiles, an approach which avoids trends and variability due to changes introduced in satellite data processing over the years.…”
Section: The Ncep/ncar and Jra-25 Reanalysesmentioning
confidence: 99%
“…Graversen et al (2008) examined temperature trends as a function of latitude and height over the period 1979-2001, based on fields from the European Centre for Medium-Range Weather Forecasts (ECMWF) ERA-40 reanalysis (Uppala et al, 2005), JRA-25, a recent effort of the Japanese Meteorological Agency (Onogi et al, 2005(Onogi et al, , 2007, and the National Centers for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR, hereafter NCEP) reanalysis (Kalnay et al, 1996). While ERA-40 documents larger positive trends in surface temperatures in the Arctic by comparison with lower latitudes in all seasons except summer, the largest Arctic trends in winter and summer lie above the surface.…”
Section: Introductionmentioning
confidence: 99%
“…It covers 26 years from 1979 to 2004. Onogi et al (2005) reported briefly the JRA-25 progress in an interim report in the first half of 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the advantages and deficiencies of JRA-25 were reported in connection with the impact of some newlyproduced observational data, which was summarized by Onogi et al (2005). In this study, we examine the characteristics of global circulation represented by the JRA-25 data, from the viewpoint of global energetics.…”
Section: Introductionmentioning
confidence: 99%